Collaborative Strategy of School and Parents in Preventing Sexual Violence Among Students at MAPN Koya Barat - Relly Misire; Yulius Mataputun; Ewendy W. Mangolo; Robert Masreng; Yuliana Waromi (SUJANA: Education and Learning Review, 2026)
Sexual violence against students in educational settings remains a critical child protection concern requiring coordinated multi-level responses. This study analyses the collaborative strategies employed between schools and parents in preventing sexual violence against students at MAPN Koya Barat, Kota Jayapura, Papua, Indonesia. A qualitative case study design was adopted, with data collected through in-depth interviews, participatory observation, and documentation study involving school principals, TPPK members, guidance and counselling teachers, homeroom teachers, student council representatives, school committee members, religious figures, school supervisors, and community leaders. Data were analysed using the interactive model of Miles, Huberman, and Saldana, incorporating reduction, display, and conclusion drawing. Findings reveal that school-parent collaboration is implemented through six integrated dimensions of parental involvement: parenting, communicating, volunteering, learning at home, decision making, and collaborating with community. Each dimension functions as a distinct protective mechanism that collectively forms a protective educational ecosystem extending child protection across institutional, family, and community levels. Cultural and religious values specific to the Papuan border community context are embedded within each dimension, strengthening the contextual applicability of the collaborative model. These findings extend Epstein's parental involvement framework beyond academic achievement toward a child protection orientation and integrate it with Bronfenbrenner's ecological model. The study offers a replicable, culturally sensitive model of school-parent collaboration relevant to faith-based and border community schools across Eastern Indonesia.